2023
DOI: 10.3389/fmars.2023.1086117
|View full text |Cite
|
Sign up to set email alerts
|

Unique bacterial communities and lifestyles in deep ocean blue holes: Insights from the Yongle Blue Hole (South China Sea)

Abstract: Deep ocean blue holes possess steep physicochemical gradients, especially low dissolved oxygen concentration, which shape the extraordinary microbial communities. However, the environmental responses of microorganisms with different lifestyles and knowledge of culturable microorganisms in the blue holes are still unknown. Here, we investigated the bacterial community structure with different lifestyles of the world’s deepest blue hole - the Yongle Blue Hole (YBH) in the South China Sea using both culture-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 82 publications
2
9
3
Order By: Relevance
“…Marine blue holes are generally characterized by steep physicochemical gradients within geographically restricted areas 1 , 13 , creating conditions for new, unidentified microbial lineages to exist 6 . High-quality metagenome-assembled genomes (MAGs) retrieved recently from the Amberjack Hole (Gulf of Mexico blue hole) showed that microbial communities were dominated by understudied microbial taxa, indicating high levels of novel microbial lineages in the Amberjack Hole 6 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Marine blue holes are generally characterized by steep physicochemical gradients within geographically restricted areas 1 , 13 , creating conditions for new, unidentified microbial lineages to exist 6 . High-quality metagenome-assembled genomes (MAGs) retrieved recently from the Amberjack Hole (Gulf of Mexico blue hole) showed that microbial communities were dominated by understudied microbial taxa, indicating high levels of novel microbial lineages in the Amberjack Hole 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies on water column microeukaryotic 9 , 10 and prokaryotic plankton 5 , 11 13 including bacteria and archaea have expanded our knowledge of the composition, structure, and potential function of the biological communities in the SYBH. The study by Liu et al 9 revealed obvious differences in the eukaryotic composition of the water column between the SYBH and the outer reef slope and demonstrated significant effects of turbidity and nitrite concentration on the eukaryotic community structure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The existence of DO, even in trace amounts, has a significant influence on microbial composition and thus biogeochemical processes. For example, at the depth of 100-120 m in March 2017, the abundance of sulfur-oxidizing bacteria (SOB) was significantly higher than that of sulfate reduction bacteria (SRB) (Yao et al, 2020;Zhou et al, 2023). The SOB is a chemolithoautotrophic microorganism living in dysoxic or suboxic conditions and deriving energy from the oxidation of thiosulfate, sulfide, or elemental sulfur to sulfate (van Vliet et al, 2021).…”
Section: Discussionmentioning
confidence: 99%